2012
DOI: 10.5713/ajas.2012.12184
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Garlic Extracts on Whole Body Amino Acid and Fatty Acid Composition, Muscle Free Amino Acid Profiles and Blood Plasma Changes in Juvenile Sterlet Sturgeon, Acipenser ruthenus

Abstract: A series of studies were carried out to investigate the supplemental effects of dietary garlic extracts (GE) on whole body amino acids, whole body and muscle free amino acids, fatty acid composition and blood plasma changes in 6 month old juvenile sterlet sturgeon (Acipenser ruthenus). In the first experiment, fish with an average body weight of 59.6 g were randomly allotted to each of 10 tanks (two groups of five replicates, 20 fish/tank) and fed diets with (0.5%) or without (control) GE respectively, at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 45 publications
3
25
2
Order By: Relevance
“…This study indicated that garlic extract contained abundant proteins, but only a few lipids. The findings conform to those Lee et al [13] who reported that garlic inhibits the synthesis of cholesterol and fatty acids in the liver; however, the exact mechanisms are not well understood. Therefore, further studies should be done to establish the relationship between the dose used, period of application.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This study indicated that garlic extract contained abundant proteins, but only a few lipids. The findings conform to those Lee et al [13] who reported that garlic inhibits the synthesis of cholesterol and fatty acids in the liver; however, the exact mechanisms are not well understood. Therefore, further studies should be done to establish the relationship between the dose used, period of application.…”
Section: Discussionsupporting
confidence: 91%
“…Spices such as mint and garlic play a very important role in fat digestion and absorption [13]. The results of the present study indicate that A. sativum plays a positive role on activities of amylase, lipase and protease.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…In this study, meat from the SFP group had higher glycogen and glucose concentrations than the control group of NSFP. It has been reported that basal diet supplementation with 5 g kg −1 garlic extract containing compounds with disulfide bonds enhanced insulin concentration, suggesting glycogen synthesis . According to previous studies, the higher residual glycogen concentration of meat improved water‐holding capacity of cooked meat .…”
Section: Discussionmentioning
confidence: 91%